Stock market integration in Central and Eastern Europe - Kurach, Radosław (Integracja rynku akcji w Europie Środkowo-Wschodniej, 2011)
In this paper we analyze stock market integration across a few CEE countries by estimating the series of regressions of the single-index Sharpe model type. We use MSCI country and regional indices to capture the size of the market (common) risk in the variance of national returns. Our results are somewhat surprising. We note the significant improvement at the stock market integration over the last years. However, the cross-country approach reveals the degree of market integration to be unrelated to the process of political and economic European integration. The results may be useful for both portfolio managers and to some extent for monetary authorities
Ekonomia = Economics, 2011, Nr 2 (14), s. 78-87
Keywords: stock market integration; diversification gains; common monetary policy